Synchronized ovulation with gonadotropin-releasing hormone, prostaglandin F and fixed-time insemination - Y. Kobayashi; Jeffrey S. Stevenson (Kansas Agricultural Experiment Station Research Reports, 1995)
Summary Lactating Holstein cows and replacement heifers were treated with a novel synchronized ovulation protocol, which involves one fixedtime insemination without heat detection. One injection of GnRH (Cystorelin®) was given, followed in 7 days with an injection of PGF2α (Lutalyse®). Approximately 32 to 36 hr later, ovulation was induced with a second injection of GnRH, and one fixed-time insemination was given 18 hr later. Control cattle were given one injection of PGF and inseminated at observed 2a estrus. Pregnancy rates measured by palpation between 38 and 52 days after insemination in controls (47.1%) were slightly, but not significantly, greater than those in the synchronized ovulation treatment (35.3%). The treatment worked much better in lactating cows than in virgin heifers. This treatment may be particularly well suited to cows in which estrus is rarely observed, as well as for synchronizing first or repeat services.; Dairy Day, 1995, Kansas State University, Manhattan, KS, 1995;
Keywords: Dairy Day; 1995; Kansas Agricultural Experiment Station contribution; no. 96-106-S; Report of progress (Kansas Agricultural Experiment Station and Cooperative Extension Service); 742; Prostaglandin; Gonadotropin-releasing hormone; Synchronized ovulation; Pregnancy rates